Process for forming an alumina powder and an alumina support substantially entirely in the form of platelets

CN122892841APending Publication Date: 2026-10-09SCIENTIFIC DESIGN LLC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202580020071.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-03-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]虽然此类技术是已知的,但每种技术都有其局限性,例如使用有害的氟化物,需要提供一种形成氧化铝粉末的新方法,所述氧化铝粉末的形貌基本上全部为片状

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application employs a fluxing agent comprising a Group 6 transition metal (i.e., Cr, Mo, or W) to provide an alumina powder that is substantially entirely platy or an alumina support that is substantially entirely platy.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications This invention claims the benefit of U.S. Provisional Patent Application No. 63 / 562,977, filed March 8, 2024, the entire contents and disclosure of which are incorporated herein by reference. Technical Field

[0002] This disclosure relates to alumina powder and alumina support having a sheet-like morphology, and more specifically to a method for forming alumina powder and alumina support having a substantially entirely sheet-like morphology. Background Technology

[0003] Flaky α-Al₂O₃ particles are crucial in the ceramics industry due to their unique physicochemical properties, such as high strength and hardness, low electrical conductivity, good thermal conductivity, and chemical resistance. Therefore, flaky alumina powder is widely used in metal, ceramic, and polymer fields, for example, as a raw material for preparing porous ceramics, including catalyst supports, as a filler in plastics, and as a matrix for pearlescent pigments. Depending on the application, various sizes and shapes of α-Al₂O₃ flaky particles are typically required. For example, reducing the particle size and altering the morphology of the flaky particles can significantly improve fracture toughness and strength in ceramic applications. However, when used as a filler in thermally conductive composites, larger flaky particles are advantageous because they generate less interparticle contact, thereby minimizing thermal resistance.

[0004] Several techniques have been developed to prepare sheet-like α-Al₂O₃ powders, such as solid-state reaction, microwave combustion, hydrothermal reaction, thermal decomposition, and molten salt synthesis. The formation mechanism of sheet-like particles will be beneficial for the design and synthesis of advanced anisotropic materials with controlled morphologies. Sheet-like alumina powders can also be formed using fluoride mineralizers and fluxes.

[0005] While such techniques are known, each technique has its limitations, such as the use of harmful fluorides. There is a need for a new method to form alumina powder, which is essentially entirely flake-shaped. Summary of the Invention

[0006] In this application, a flux containing a Group 6 transition metal (i.e., Cr, Mo, or W) is used to provide alumina powder or alumina support that is substantially entirely flake-shaped. Throughout this disclosure, the term "substantially entirely" means that the alumina powder and the alumina support have a flake-shaped morphology of greater than 96%, preferably 97%, 98%, or 99%, more preferably 100%.

[0007] In one aspect of this application, a method for forming substantially entirely flake-shaped alumina powder is provided. In one embodiment, the method includes: forming an aqueous slurry comprising an alumina source and a flux, wherein the flux has the chemical formula MO3, wherein M is a metal selected from Cr, Mo, and W, and wherein the flux is present in the aqueous slurry in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the alumina source; drying the slurry to provide a solid product; and calcining the solid product at a temperature above about 1200°C to convert the solid product into substantially entirely flake-shaped alumina powder.

[0008] In another aspect of this application, a method for forming an alumina support that is substantially entirely sheet-like is provided. In one embodiment, the method includes: adding a flux to a support composition comprising an alumina source, wherein the flux has the chemical formula MO3, wherein M is a metal selected from Cr, Mo, and W, and wherein the flux is added in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the alumina source; mixing the flux and the support composition to provide an admixture of the flux and the support composition; molding the admixture into a molded body; and calcining the molded body at a temperature above about 1200°C to convert the molded body into an alumina support that is substantially entirely sheet-like. Attached Figure Description

[0009] Figure 1 This is a scanning electron microscope (SEM) image of alumina powder 1 from Example 1.

[0010] Figure 2 This is a SEM image of alumina powder 2 from Example 1.

[0011] Figure 3 This is a SEM image of alumina powder 3 from Example 1.

[0012] Figure 4 This is an SEM image of alumina powder 4 from Example 1.

[0013] Figure 5 This is a SEM image of alumina powder 5 from Example 1.

[0014] Figure 6 This is a SEM image of alumina powder 6 from Example 1.

[0015] Figure 7 This is an SEM image of alumina powder 7 from Example 1.

[0016] Figure 8 This is a SEM image of alumina powder 8 from Example 1.

[0017] Figure 9 This is a SEM image of alumina powder 9 from Example 2.

[0018] Figure 10 This is an SEM image of alumina powder 10 from Example 2.

[0019] Figure 11 This is a SEM image of alumina powder 11 from Example 2.

[0020] Figure 12 This is an SEM image of alumina powder 12 from Example 2.

[0021] Figure 13 This is a SEM image of alumina powder 13 from Example 2.

[0022] Figure 14 This is an SEM image of alumina powder 14 from Example 2.

[0023] Figure 15 This is an SEM image of alumina powder 15 from Example 2.

[0024] Figure 16 The graphs show the mercury porosimetry (HgPVD) distribution of various α-alumina supports (i.e., supports 1-4 in Examples 3).

[0025] Figure 17 SEM image of the fracture surface of the α-alumina support (i.e., support 1 in Example 3) according to this disclosure.

[0026] Figure 18 SEM image of the fracture surface of the α-alumina support (i.e., support 2 in Example 3) according to this disclosure.

[0027] Figure 19 SEM image of the fracture surface of the α-alumina support (i.e., support 3 in Example 3) according to this disclosure.

[0028] Figure 20A SEM image of the fractured surface of the α-alumina carrier (i.e., carrier 4 of Example 3) before washing, according to this disclosure.

[0029] Figure 20B SEM image of the fractured surface of the α-alumina carrier (i.e., carrier 4 of Example 3) after washing, according to the present disclosure.

[0030] Figure 21 To illustrate the mercury porosimetry (HgPVD) curves of the α-alumina support according to this disclosure before and after washing.

[0031] Detailed Implementation Plan The present disclosure will now be described in more detail with reference to the following discussion and the accompanying drawings. In the following description, numerous specific details, such as particular structures, components, materials, dimensions, processing steps, and techniques, are set forth in order to provide an understanding of various embodiments of the present disclosure. However, those skilled in the art will understand that various embodiments of the present disclosure can be implemented without these specific details. As used throughout the present disclosure, the term “about” generally means a difference from a numerical value not exceeding ±10%, ±5%, ±2%, ±1%, or ±0.5%. When a range in the present disclosure is expressed as a range from one numerical value to another (e.g., 20 to 40), the present disclosure covers any numerical value falling within that range (i.e., 22, 24, 26, 28.5, 31, 33.5, 35, 37.7, 39, or 40) or any quantity defined by any two numerical values ​​that may exist within that range (e.g., 28.5-35).

[0032] The terminology used herein is for describing particular embodiments only and is not intended to limit this disclosure. As used herein, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “described” are intended to include the plural forms as well. It should also be understood that when the terms “comprising” and / or “including” are used in this disclosure, they mean the presence of the stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or combinations thereof.

[0033] I. Formation of flake-shaped alumina powder A method for forming alumina powder that is substantially entirely in a flake-like morphology will now be described in more detail. This method includes forming an aqueous slurry comprising an alumina source and a flux. In this application, the aqueous slurry is a mixture containing at least an alumina source suspended in water. In this disclosure, the slurry may have a solids content of about 25% to 50%, more preferably about 30% to 45%. Other solids contents are also feasible and may be used, provided that the solids content allows for uniform dispersion of the flux. The solids content constitutes the amount of alumina source and other optional solid components (e.g., silica) that may be included in the slurry.

[0034] In this disclosure, the alumina source that can be used in the methods of this disclosure includes any alumina compound commonly used to form alumina powder. The term "alumina" is used throughout this disclosure to refer to alumina. In embodiments of this disclosure, the alumina source may be a single alumina compound or a mixture of two or more alumina compounds. In embodiments of this disclosure, the alumina source is transition alumina. The transition alumina that can be used in this disclosure may be in various crystalline phases, such as γ, θ, and κ. In some embodiments of this disclosure, transition alumina containing hydrated alumina is preferred. Examples of hydrated alumina that can be used as an alumina source in this disclosure include, but are not limited to, boehmite (γ-AlOOH), gibbsite (α-Al(OH)3), or mixtures thereof. The alumina source that can be used in this disclosure is available from a wide range of suppliers, including, for example, GNPGraystar and Nabaltec.

[0035] In embodiments of this disclosure, the alumina source may have an average particle size D50 of about 0.1 µm to about 20 µm, more preferably an average particle size of about 0.3 µm to 15 µm. In this disclosure, the average particle size D50 represents the size of half of the particles being below a given value and the size of half of the particles being above a given value. The average particle size D50 reported in this disclosure can be determined by particle size analysis.

[0036] The alumina source used in this disclosure may contain various impurities present in the alumina source, i.e., unintentionally added components. Exemplary embodiments of such impurities present in the alumina source include, but are not limited to, SiO2, Na2O, Fe2O3, and mixtures thereof. In this disclosure, the total impurity content in the alumina source is typically about 4000 ppm or less, more preferably about 100 ppm to 500 ppm.

[0037] In addition to the alumina source, the slurry may also contain additional solid components intentionally added to the slurry. Additional solid components that can be used in this disclosure may be shape control agents, such as silicon, silicon compounds, germanium, or germanium compounds. When present, the additional solid component may be present in the slurry in an amount of about 0.1 wt% to about 5 wt%, more preferably about 0.3 wt% to about 0.5 wt%, based on the total weight of the alumina source. In an exemplary embodiment of this disclosure, silica is used as an additional solid component that may be present in the slurry. When silica is used, silica is present in the slurry in an amount of about 0.1 wt% to about 5 wt%, more preferably about 0.1 wt% to about 0.3 wt%, based on the total weight of the alumina source.

[0038] As mentioned above, the slurry is an aqueous slurry, in which water is used as a solvent. The water is typically deionized water.

[0039] As described above, a flux is also present in the aqueous slurry. The term "flux" is used throughout this disclosure to refer to a compound that promotes the formation of flake-like particles. Fluxes that can be used in this disclosure have the chemical formula MO3, where M is a metal selected from Cr, Mo, and W. In one preferred embodiment, M is Mo, and the flux is MoO3. In another preferred embodiment, M is W, and the flux is WO3. Fluxes are typically added in the form of metal complexes comprising ammonium and the aforementioned MO3 moiety. In such complexes, ammonium readily dissociates from the MO3 moiety upon heat treatment.

[0040] In embodiments of the present disclosure that form substantially entirely flake-shaped alumina powder, a flux is present in the aqueous slurry in an amount of about 0.1% to about 10% by weight, more preferably about 0.5% to about 5% by weight, and even more preferably about 2% to about 4% by weight, based on the total weight of the alumina source.

[0041] A slurry is formed by adding an alumina source, optional shape control agent or other solid components, and a flux to water. The addition of the alumina source, optional shape control agent or other solid components, and flux can vary. In embodiments, it is preferred to add the flux to a mixture of water, the alumina source, and optional shape control agent. Conventional slurry processes known to those skilled in the art can be used to form the slurry. Slurry formation is typically carried out under continuous stirring and is typically at a nominal room temperature. In this disclosure, nominal room temperature can be defined as a temperature from about 18°C ​​to about 25°C.

[0042] The method for forming substantially entirely flake-like alumina powder continues by drying the slurry to provide a solid product, which typically has a certain degree of moisture content. In some embodiments, the solid product may have a moisture content of about 1% to about 10% by weight. That is, the drying step of this disclosure does not provide a completely moisture-free solid product. Instead, the drying step partially removes water from the solid product. In embodiments of this application, the drying step is carried out at a temperature of about 50°C to about 90°C, more preferably about 70°C to about 80°C. The drying step can be carried out using conventional drying equipment known to those skilled in the art. In one exemplary embodiment, the drying step is carried out under a heat lamp.

[0043] Following drying, the method for forming substantially entirely flake-like alumina powder continues by calcining (i.e., firing) the solid product at a temperature of about 1200°C or higher, more typically from about 1100°C to about 1500°C. A single, continuous calcination temperature can be used, or various heating and holding cycles can be used during the calcination step. Depending on the exact calcination temperature used, the calcination step can be carried out for varying durations. Typically, calcination is carried out for a period of 1 hour to 15 hours, more preferably from about 3 hours to 10 hours. During the calcination step, the solid product is typically exposed to air. The above-described calcination conditions are sufficient to remove any residual solvent present in the solid product. The above-described calcination conditions are also sufficient to remove at least a portion of the flux content from the alumina powder produced by the method of this disclosure.

[0044] The calcination step transforms the solid product into alumina powder that is substantially entirely flake-like. This substantially flake-like alumina powder is typically α-alumina powder. The alumina powder produced by the method of this application is characterized by having a flake particle content of greater than 96%, preferably 97%, 98%, or 99%, more preferably 100%. The substantially flake-like alumina powder has a flake particle aspect ratio of about 1:1 or greater, more preferably about 5:1 to about 10:1. In this disclosure, the flake particle aspect ratio is the ratio of the width to the height of the flake particles, and the range of flake particle aspect ratios reported herein represents the average value measured for each flake particle within the alumina powder. The flake particle aspect ratio can be determined by measurement using SEM images of the powder.

[0045] The substantially entirely flake-shaped alumina powder formed by the method of this disclosure can have an average particle size of about 0.1 µm to about 5 µm, more preferably about 1 µm to 2 µm. The substantially entirely flake-shaped alumina powder formed by the method of this disclosure can have an average particle size of about 0.1 µm to about 5 µm. 2 / g to approximately 5m 2 / g of surface area, more preferably about 1m 2 / g to approximately 2m 2 / g of surface area.

[0046] The substantially entirely flake-shaped alumina powder produced by the method of this disclosure can be widely used in the fields of metals, ceramics, and polymers, as well as in porous ceramics including catalyst supports, as a filler in plastics, and as a matrix for pearlescent pigments. In a highly preferred embodiment of this disclosure, the substantially entirely flake-shaped alumina powder formed by the method of this application can be used to form catalyst supports, particularly ethylene oxide (EO) catalyst supports. When forming EO catalyst supports, the substantially entirely flake-shaped alumina powder formed using the method of this application can be used as one of the alumina sources used in any EO catalyst support preparation method.

[0047] II. Formation of sheet-like alumina carriers The method for forming an alumina support that is substantially entirely lamellar in morphology will now be described in more detail. The method for forming an alumina support that is substantially entirely lamellar includes adding a flux to the support composition. In this aspect of the application, the flux used in the method for forming a substantially lamellar alumina support is the same as the flux used in forming substantially lamellar alumina powder described above. That is, the flux used to form substantially lamellar alumina has the chemical formula MO3, where M is a metal selected from Cr, Mo, and W. In a preferred embodiment, M is Mo, and the flux is MoO3. In another preferred embodiment, M is W, and the flux is WO3. The flux is typically added in the form of a metal complex comprising ammonium and the aforementioned MO3 moiety.

[0048] In embodiments forming the substantially entirely sheet-like alumina carrier of this disclosure, flux is added to the carrier composition in an amount of about 0.5% to about 5% by weight, more preferably about 1% to about 3% by weight, and even more preferably about 2% to about 2.5% by weight, based on the total weight of the alumina source providing a portion of the carrier composition.

[0049] The alumina source providing a portion of the carrier composition includes one of the alumina sources mentioned above in forming a substantially entirely flake-like alumina powder. In embodiments of this disclosure, the alumina source may be a single alumina compound or a mixture of two or more alumina compounds. In embodiments of this disclosure, the alumina source is transition alumina. The transition alumina used in this disclosure may be in various crystalline phases, such as γ, θ, and κ. In some embodiments of this disclosure, transition alumina containing hydrated alumina is preferred. Examples of hydrated alumina that can be used as the alumina source for forming the carrier in this disclosure include, but are not limited to, boehmite (γ-AlOOH), gibbsite (α-Al(OH)3), or mixtures thereof.

[0050] In embodiments of this disclosure, the alumina source may have an average particle size D50 of about 0.1 µm to about 20 µm, more preferably an average particle size of about 0.3 µm to 15 µm. In embodiments of this disclosure, the alumina source may have an average particle size D50 of about 10 µm. 2 / gm to approximately 200m 2 A surface area of ​​ / gm, more preferably a surface area of ​​about 15m² 2 / gm to approximately 180m 2 / g.

[0051] The alumina source used in this disclosure may contain various impurities present in the alumina source, i.e., unintentionally added components. Exemplary embodiments of such impurities present in the alumina source include, but are not limited to, SiO2, Na2O, Fe2O3, and mixtures thereof. In this disclosure, the total impurity content in the alumina source is typically about 4000 ppm or less, more preferably about 100 ppm to 500 ppm.

[0052] In addition to the alumina source, the carrier composition of this application may also contain additional solid components intended for forming the carrier composition. Additional solid components that can be used in this disclosure may be shape control agents, such as silicon, silicon compounds, germanium, or germanium compounds. When present, the additional solid component may be used in an amount of about 0.1 wt% to about 5 wt%, more preferably about 0.3 wt% to about 0.5 wt%, based on the total weight of the alumina source. In an exemplary embodiment of this disclosure, silica is used as the additional solid component. When silica is used, silica is present in an amount of about 0.1 wt% to about 0.7 wt%, more preferably about 0.3 wt% to about 0.5 wt%, based on the total weight of the alumina source.

[0053] In some embodiments of this disclosure, the carrier composition may further comprise a burnout material. Exemplary burnout materials that can be used in this disclosure include, but are not limited to, polypropylene, polyethylene, carbohydrates, gums, flour, proteins, lignin, resins, waxes, alcohols, and esters. When used, the burnout material may be present in the carrier composition in an amount of about 1% to about 10% by weight, more preferably about 5% to about 9% by weight, relative to the total amount of alumina source present in the carrier composition. In some embodiments, no burnout material is used when forming the substantially entirely sheet-like alumina carrier of this disclosure.

[0054] In some embodiments, the carrier composition may also comprise a non-silicate binder, a lubricant, a solvent, or any combination of these components. The non-silicate binder may include, for example, boehmite (γ-AlOOH). Typically, the non-silicate binder is dispersed in deionized water. The lubricant may include any conventional lubricant, such as petrolatum. The amount of lubricant that may be added at this stage of the disclosure may comprise the total amount or a portion of the lubricant used to form the alumina carrier of the disclosure.

[0055] After the flux is added to the carrier composition or during the addition process itself, mixing is employed to provide a blend of the flux and the carrier composition (as well as any other carrier composition components mentioned above). This blend may be referred to as a precursor carrier mixture. This mixing provides a homogeneous blend. The mixing step can be carried out using any conventional mixing equipment, and the speed and duration of the mixing step can be varied, and the formation of a homogeneous mixture is necessarily crucial in this disclosure.

[0056] The blend is then shaped to provide a molded article. The shape of the molded article can vary. Molding of the article is typically performed by pressing, extrusion, molding, casting, etc. In some preferred embodiments of this disclosure, extrusion can be performed using an extrusion die capable of producing a hollow cylindrical shape, which is then cut into substantially equal-length segments. The cut extrudate is then dried using any conventional drying method. The dried extrudate can then be transferred to a furnace to remove water and burn off most of any ignition-depleted material and other organic components present. Depending on the type of ignition-depleted material, heat treatment can be performed at temperatures ranging from 100°C to 1,000°C, with heating rates varying between 10°C / hr and 100°C / hr.

[0057] Subsequently, the extrudate can be calcined (i.e., sintered) at a temperature of about 1100°C or higher, preferably about 1250°C to about 1600°C, to transform the blend into an alumina support that is substantially entirely flake-like. The calcination step used in forming the alumina support can be carried out in air, an inert environment, or any combination thereof. In one embodiment, the calcination step can be carried out in flowing air. After the calcination step, the resulting alumina support is cooled to room temperature. The heating and cooling rates can be in the range of 1°C / min to 5°C / min. In this disclosure, other heating and cooling rates in the range of 0.5°C / min to 20°C / min can also be used to provide the alumina support.

[0058] The alumina support formed using the above method is an alumina support that is substantially entirely flake-like. Alumina supports that are substantially entirely flake-like are typically α-alumina supports. The alumina support produced by the method of this application is characterized by having a flake particle content of greater than 96%, preferably 97%, 98%, or 99%, more preferably 100%. The substantially flake-like alumina support has a flake particle aspect ratio of about 5:1 or greater, more preferably about 10:1 to about 20:1. In this disclosure, the flake particle aspect ratio is the ratio of the width of the flake particles to the height of the flake particles, and the range of flake particle aspect ratios reported herein represents the average value of each flake particle measured within the alumina support. The flake particle aspect ratio can be determined by SEM measurement.

[0059] The flux content in the substantially flake-shaped alumina carrier can be reduced by washing it. Washing may include water washing, which may be performed once or multiple times (i.e., multiple washings can be used to reduce the flux content in the substantially flake-shaped alumina carrier).

[0060] The alumina carrier disclosed herein is substantially entirely sheet-like and has a thickness of approximately 0.2 m. 2 / gm to approximately 2m 2 Surface area per gm, more preferably about 1.5 m² 2 / gm to approximately 2.0m 2 / gm surface area. The substantially entirely sheet-like alumina support of this disclosure has a water absorption rate of about 30% to about 90%, more preferably about 40% to about 85%. The water absorption rate is determined herein by typical water absorption rate measurements known in the art. The substantially entirely sheet-like alumina support of this disclosure has a mercury injection pore volume of about 0.3 ml / g to about 0.9 ml / g, more preferably about 0.4 ml / g to about 0.85 ml / g. The substantially entirely sheet-like alumina support of this disclosure has an average crushing strength of about 50 N to about 300 N, more preferably about 100 N to about 200 N.

[0061] In some embodiments, in the substantially entirely sheet-like alumina support, the proportion of pore volume with a pore size less than 0.3 µm to the total pore volume is less than 1%, preferably less than 0.1%. In some embodiments of this disclosure, the modal pore size of the substantially entirely sheet-like alumina support is in the range of about 0.1 µm to about 10 µm, more preferably in the range of about 1 µm to about 3 µm.

[0062] III. Catalysts supported on sheet-like alumina supports In another embodiment, the aforementioned sheet-like alumina support can be used as a catalyst support (i.e., catalyst proppant), in which case it typically comprises one or more catalytically active materials, usually metals, disposed on or within the sheet-like alumina support. These one or more catalytically active materials can catalyze specific reactions and are well known in the art. In some embodiments, the catalytically active materials include one or more transition metals and / or lanthanides from Groups 3-14 of the periodic table. In such applications, one or more promoters (i.e., substances that assist specific reactions) may also be disposed on or within the porous body of this disclosure. These one or more promoters may be, for example, alkali metals, alkaline earth metals, transition metals, and / or elements from Groups 15-17 of the periodic table.

[0063] In embodiments where the sheet-like alumina support of this disclosure is used as a support for a silver-based epoxidation catalyst, the sheet-like alumina support includes silver on and / or within the support. Therefore, in the methods described above, silver is typically incorporated into the sheet-like alumina support in a manner known in the art (e.g., by impregnation with silver salt followed by heat treatment, as is known in the art, such as in U.S. Patents 4,761,394, 4,766,105, 4,908,343, 5,057,481, 5,187,140, ​​5,102,848, 5,011,807, 5,099,041, and 5,407,888, all of which are incorporated herein by reference). The concentration of the silver salt in the solution is typically in the range of about 0.1% by weight to the maximum value allowed by the solubility of the particular silver salt in the solubility solvent employed. More typically, the concentration of silver salt is from about 0.5 wt% silver to 45 wt% silver, or even more typically, from about 5 wt% silver to 35 wt% silver based on the weight of the lamellar alumina support. These amounts are also typically the weight content found in the catalyst after heat treatment. For suitability as an ethylene epoxidation catalyst, the amount of silver should be a catalytically effective amount for ethylene epoxidation, which can be any amount provided above.

[0064] In addition to silver, the silver-based epoxidation catalyst of the present invention may further include any one or more promoting substances in a promoting amount. These one or more promoting substances may be incorporated into the sheet-like alumina support of the present disclosure before, during, or after silver deposition. As used herein, the “promoting amount” of a component of the catalyst refers to the amount of that component that effectively provides one or more improvements in the catalyst’s catalytic performance compared to a catalyst without said component.

[0065] For example, silver-based epoxidation catalysts may contain promoting amounts of Group I alkali metals or mixtures of two or more Group I alkali metals. Suitable Group I alkali metal promoters include, for example, lithium, sodium, potassium, rubidium, cesium, or combinations thereof. Cesium is generally preferred, and combinations of cesium with other alkali metals are also preferred. The amount of alkali metal is typically from about 10 ppm to about 3000 ppm by weight of the total catalyst, more typically from about 15 ppm to about 2000 ppm, more typically from about 20 ppm to about 1500 ppm, and even more typically from about 50 ppm to about 1000 ppm, based on the alkali metal content.

[0066] Silver-based epoxidation catalysts may also contain a promoting amount of a Group 2 alkaline earth metal or a mixture of two or more Group 2 alkaline earth metals. Suitable alkaline earth metal promoters include, for example, beryllium, magnesium, calcium, strontium, and barium, or combinations thereof. The amount of alkaline earth metal promoter is similar to that of the alkali metal promoters described above.

[0067] The silver-based epoxidation catalyst may also contain a promoting amount of a main group element or a mixture of two or more main group elements. Suitable main group elements include any element from Group 13 (Boron Group) to Group 17 (Halogen Group) of the periodic table. In one embodiment, a promoting amount of one or more sulfur compounds, one or more phosphorus compounds, one or more boron compounds, or a combination thereof may be used.

[0068] Silver-based epoxidation catalysts may also contain a promoting amount of transition metal or a mixture of two or more transition metals. Suitable transition metals may include, for example, elements and combinations thereof from Group 3 (scandium), Group 4 (titanium), Group 5 (vanadium), Group 6 (chromium), Group 7 (manganese), Groups 8-10 (iron, cobalt, nickel), and Group 11 (copper) of the periodic table. More typically, the transition metal is an early transition metal selected from Groups 3, 4, 5, 6, or 7 of the periodic table, such as hafnium, yttrium, molybdenum, tungsten, rhenium, chromium, titanium, zirconium, vanadium, tantalum, niobium, or combinations thereof.

[0069] In one embodiment of this disclosure, the silver-based epoxidation catalyst comprises silver, cesium, and rhenium. In another embodiment of this disclosure, the silver-based epoxidation catalyst comprises silver, cesium, rhenium, and one or more substances selected from Li, K, W, Zn, Mo, Mn, and S.

[0070] Silver-based epoxidation catalysts may also contain a promoting amount of rare earth metals or a mixture of two or more rare earth metals. Rare earth metals include any element with atomic numbers 57-71, yttrium (Y), and scandium (Sc). Some examples of these elements include lanthanum (La), cerium (Ce), and samarium (Sm).

[0071] Transition metal or rare earth metal promoters are typically present in amounts from about 0.1 μmol / g to about 10 μmol / g, more typically from about 0.2 μmol / g to about 5 μmol / g, or even more typically from about 0.5 μmol / g to about 4 μmol / g of total catalyst, in metal terms. All of the above promoters, except for alkali metals, can be in any suitable form, including, for example, zero-valent metals or higher-valent metal ions.

[0072] Silver-based epoxidation catalysts may also contain an amount of rhenium (Re), which is known to be a particularly effective promoter for highly selective catalysts used in the epoxidation of ethylene. The rhenium component in the catalyst can be in any suitable form, but more typically as one or more rhenium-containing compounds (e.g., rhenium oxide) or complexes. Rhenium may be present, for example, in amounts from about 0.001 wt% to about 1 wt%. More typically, based on the weight of the total catalyst including the support, rhenium is present, for example, in amounts from about 0.005 wt% to about 0.5 wt%, or even more typically from about 0.01 wt% to about 0.05 wt%, as rhenium metal. All these promoters, except alkali metals, can be in any suitable form, including, for example, zero-valent metals or higher-valent metal ions.

[0073] After impregnation with silver and any accelerator, the impregnated sheet alumina support is removed from the solution and calcined for a time sufficient to reduce the silver component to metallic silver and remove volatile decomposition products from the silver-containing support. Calcination is typically accomplished by heating the impregnated sheet alumina support (preferably at a gradual rate) to a temperature in the range of about 200°C to about 600°C, more typically about 200°C to about 500°C, more typically about 250°C to about 500°C, more typically about 200°C, or 300°C to about 450°C, at a reaction pressure in the range of about 0.5 to about 35 bar. Generally, the higher the temperature, the shorter the required calcination time. Various heating time periods for heat treatment of impregnated supports have been described in the art. See, for example, U.S. Patent No. 3,563,914, which indicates heating for less than 300 seconds, and U.S. Patent No. 3,702,259, which discloses heating at temperatures from 100°C to 375°C for 2 to 8 hours to reduce silver salts in a catalyst. For this purpose, continuous or stepped heating procedures can be used. During calcination, the impregnated support is typically exposed to a gaseous atmosphere containing an inert gas such as nitrogen. The inert gas may also contain a reducing agent.

[0074] On the other hand, this disclosure relates to a method for the gas-phase production of ethylene oxide by converting ethylene to ethylene oxide in the presence of oxygen using the aforementioned silver-based epoxidation catalyst. Typically, the ethylene oxide production process is carried out by continuously contacting an oxygen-containing gas with ethylene in the presence of a catalyst at temperatures ranging from about 180°C to about 330°C, more typically from about 200°C to about 325°C, and more typically from about 225°C to about 270°C, with pressures varying from about atmospheres to about 30 atmospheres depending on the desired mass rate and productivity. Pressures are typically used in the range of about atmospheres to about 500 psi. However, higher pressures can be used within the scope of this invention. Residence times in large-scale reactors are typically on the order of about 0.1 to about 5 seconds. A typical method for the oxidation of ethylene to ethylene oxide involves oxidizing ethylene in the molecular oxygen phase in a fixed-bed tubular reactor in the presence of the catalyst of this invention. Conventional commercial fixed-bed ethylene oxide reactors are typically in the form of multiple parallel elongated tubes (in a suitable shell). In one embodiment, the tube has an outer diameter of approximately 0.7 to 2.7 inches, an inner diameter of 0.5 to 2.5 inches, and a length of 15 to 45 feet, and is filled with catalyst.

[0075] In some embodiments, the silver-based epoxidation catalyst described above exhibits high selectivity in the reaction of ethylene with molecular oxygen to ethylene oxide. For example, selectivity values ​​of at least about 83 mol% to about 93 mol% can be achieved. In some embodiments, the selectivity is about 87 mol% to about 93 mol%. The conditions for carrying out such an oxidation reaction in the presence of the silver-based epoxidation catalyst described above generally include those described in the prior art. This applies to, for example, suitable temperature, pressure, residence time, diluent material (e.g., nitrogen, carbon dioxide, steam, argon, and methane), the presence or absence of a regulator for controlling the catalytic action (e.g., 1,2-dichloroethane, vinyl chloride, or chloroethane), the desire to employ cyclic operation or apply continuous conversion in different reactors to increase the yield of ethylene oxide, and any other specific conditions selectable in the method for preparing ethylene oxide.

[0076] In the production of ethylene oxide, the reactant feed mixture typically contains about 0.5% to about 45% ethylene and about 3% to about 15% oxygen, with the balance consisting of relatively inert materials, including substances such as nitrogen, carbon dioxide, methane, ethane, and argon. Typically, only a portion of the ethylene reacts with each pass through the catalyst. After separating the desired ethylene oxide product and removing appropriate purge streams and carbon dioxide to prevent the uncontrolled accumulation of inert products and / or byproducts, the unreacted material is usually returned to the oxidation reactor.

[0077] The following examples are provided to further illustrate this disclosure. The scope of this disclosure is in no way limited to the examples listed herein. In the following examples, various hydrated alumina powders are used as the alumina source. Table 1 provides a list of the various hydrated alumina powders used in the examples of this disclosure. Table 1 also includes values ​​for the average particle size (D50), surface area (SA), and major impurities for each hydrated alumina powder listed in Table 1.

[0078] Table 1: Hydrated Alumina Powder Example 1: Formation of tungsten oxide-assisted flake alumina powder In this embodiment, various alumina powders were prepared using WO3 flux. Notably, the mixture compositions 1-8 identified in Table 2A were prepared by forming slurries of hydrated alumina powders listed in Table 2A and further identified in Table 1 with various amounts of silica and WO3 also listed in Table 2A in deionized (DI) water. The slurry solids content of each of the mixture compositions 1-8 is provided in Table 2B.

[0079] Table 2A: Mixture compositions for preparing flake alumina powder using WO3 flux 1 WO3 comes from (NH4)6H2W 12 O 40 After forming the mixture compositions listed in Table 2A, these mixture compositions are dried under a heating lamp and calcined using the conditions listed in Table 2B.

[0080] Table 2B: Experimental conditions for preparing flake-shaped alumina powder using WO3 flux Following the calcination process, alumina powders 1-8 were prepared from mixtures 1-8, respectively. As described in Table 2C, alumina powders 1, 2, 7, and 8 have 100% flake morphology, while alumina powder 3 has essentially 100% flake morphology. Alumina powders 4-6 have some (less than 95%) or no alumina flake particles.

[0081] Table 2C: Analysis of flake alumina powder using WO3 flux It is noteworthy that 100% lamellar alumina with a high aspect ratio was observed to form (alumina powders 1-3 listed in Table 2C) at silica as low as 0.9 wt.% and WO3 as 2.6 wt.%. This can be achieved... Figure 1(SEM image of alumina powder 1) Figure 2 (SEM of alumina powder 2) and Figure 3 As seen in the SEM image (SEM of alumina powder 3), when silica and WO3 were further reduced to half the level of mixture composition 3, some flaky particles still formed, but most alumina particles remained equiaxed (see Table 2C for results listed for alumina powder 4; and...). Figure 4 SEM images of alumina powder 4 shown. No flaky alumina was observed even at silica and WO3 levels below those of mixture composition 4 (see Table 2C for results listed for alumina powders 5 and 6; and respectively). Figure 5 and Figure 6 SEM images of alumina powders 5 and 6 shown.

[0082] When different hydrated alumina powders are studied, namely gibbsite-2 in mixture composition 7 and boehmite-1 in mixture composition 8, instead of gibbsite-1 used in mixture compositions 1-6, alumina powder with 100% alumina flake particles is formed, see, for example, alumina powder 7 and Figure 7 SEM images of alumina powder 7 and alumina powder 8 shown. Figure 8 SEM images of alumina powder 8 shown. Both alumina powder 7 and alumina powder 8 exhibit different flaky particle characteristics from alumina powders 1-3, such as shape and thickness. These variations suggest that the flaky morphology can be controlled by changing the choice of hydrated alumina powder used in the initial mixture composition.

[0083] exist Figure 1 The white spots observed in alumina powder 1 have been qualitatively identified as tungsten. Semi-quantitative analysis of alumina powders 1, 7, and 8 confirmed the presence of WO3; however, the WO3 levels were significantly lower than calculated levels. The loss of some WO3 may be due to sublimation during the high-temperature calcination process used to form the respective alumina powders.

[0084] Example 2: Formation of molybdenum oxide-assisted alumina powder flake particles In this embodiment, various alumina powders were prepared using MoO3 flux. Notably, the mixture compositions 9-15 identified in Table 3A were prepared by forming slurries of hydrated alumina powders listed in Table 3A and further identified in Table 1 with various amounts of silica and MoO3 also listed in Table 3A in deionized (DI) water. The slurry solids content of each of the mixture compositions 9-15 is provided in Table 3B. Based on the data provided in Example 1 above, the levels of silica and MoO3 were kept relatively narrow, starting with 0.5% silica and 2.5% MoO3, using either gibbsite-2 or boehmite-2.

[0085] Table 3A: Mixture compositions for preparing flake alumina powder using MoO3 flux 1 Ammonium molybdate tetrahydrate (82% MoO3) After forming the mixture compositions listed in Table 3A, these mixture compositions are dried under a heating lamp and calcined using the conditions listed in Table 3B.

[0086] Table 3B: Experimental conditions for preparing flake-shaped alumina powder using MoO3 flux Following the calcination process, alumina powders 9-15 were prepared from the mixture compositions 9-15. As described in Table 3C, alumina powders 9-10 and 12-15 had 100% flake morphology, while alumina powder 11 had essentially 100% flake morphology.

[0087] Table 3C: Analysis of flake alumina powder using MoO3 flux Comparing alumina powder 9 and alumina powder 10, it is clear that alumina powder 10, prepared using boehmite-2, exhibits a similar flaky particle size to alumina powder 9 prepared using gibbsite-2, but the flaky particles are much thinner; note that boehmite-2 is finer than gibbsite-2 (see Table 1). Therefore, alumina powder 10 will have a much higher aspect ratio, which translates to a higher surface area than alumina powder 9. SEM images of alumina powder 9 and alumina powder 10 are shown in Table 1. Figure 9 and Figure 10 middle.

[0088] Alumina powder 11 is prepared with lower levels of silica and MoO3 than either alumina powder 9 or alumina powder 10, and as... Figure 11The SEM images provided show that alumina powder 11 exhibits a large number of flaky particles. This demonstrates that the particle size and morphology of the resulting alumina can be controlled by varying the levels of silica and MoO3.

[0089] To further investigate the effects of silica and MoO3 and their ratio on morphology, for the same boehmite-based samples, silica was varied between 0.2 wt.% and 0.9 wt.%, while MoO3 was varied between 1.9 wt.% and 3.7 wt.%, as shown in Tables 3A and 3C for mixture compositions 12-15 and alumina powder 12-15. Figure 12-15 In the mixture composition 12, silica was reduced to an extremely low level of 0.2 wt.% while maintaining a relatively high level of MoO3, resulting in alumina powder 12 having thicker, flaky particles (see [link]). Figure 12 (SEM shown), while increasing silica to 0.9 wt.% while maintaining MoO3 at 2.4 wt.% in mixture composition 13 indeed prepared alumina powder 13 with thinner and smaller flake particles (see, for example). Figure 13 (SEM image shown). Based on these findings, it appears that a sufficient amount of silica is required to produce thinner, sheet-like particles (higher aspect ratio).

[0090] The alumina powder 14 prepared from the mixture composition 13 has a high MoO3 content of 3.7 wt.% and a silica content of 0.5 wt.%. Figure 14 SEM images showed some larger but relatively thin flake-like particles. When 0.5 wt.% silica and 1.9 wt.% MoO3 were applied to the boehmite-2-based composition mixture 15, alumina powder 15 was observed to have a relatively thinner flake-like morphology (high aspect ratio) (see example). Figure 15 (SEM shown in the image).

[0091] Another observation regarding the formation of MoO3-assisted α-alumina powder is that the MoO3 content in the final flake-like alumina powder was significantly lower than the calculated MoO3 loading (see alumina powders 9-10). XRF analysis showed only about 0.22 wt.%–0.27 wt.% MoO3, while about 2.5 wt.% was introduced, representing a loss of approximately 90% of the MoO3 during the process. Significant sublimation likely occurred during high-temperature calcination. Due to the high solubility of MoO3, the remaining free MoO3 can be further removed by washing with water or dilute alkali.

[0092] Example 3: Formation of sheet-like alumina carrier In this embodiment, WO3 and MoO3 fluxes are incorporated into the carrier formation method based on hydrated alumina to produce flake-like alumina in situ. The carrier formulations used to form carriers 1-4 are shown in Table 4A. Each of carriers 1-4 is prepared by adding the fluxes (i.e., WO3 and MoO3) listed in Table 4A in the amounts disclosed therein to a carrier composition containing one of the alumina powders identified in Table 4A. The resulting mixtures are then mixed to provide an admixture, which is subsequently extruded. Each extruded admixture is then calcined at a temperature of approximately 1250°C to convert the extruded admixture into an α-alumina carrier. The physical properties of each of the formed carriers 1-4 are summarized in Tables 4B and 4C.

[0093] Table 4A: Carrier Formulation 1. Finely micronized polypropylene powder from Micro Powders, Inc. 2. Industrial white petrolatum (USP grade) manufactured by Caseway Industrial Products, Inc. Table 4B: Carrier Properties Table 4C: XRF analysis data of the vector Carrier 1 exhibits high water absorption, relatively low surface area, and very low crushing strength. Figure 16 HgPVD in the study showed a single-mode pore size distribution centered at approximately 2.3 µm, with no pores smaller than 0.3 µm observed. Figure 17 SEM analysis of the fracture surface of carrier 1 showed a completely sheet-like, very uniform sheet morphology, with sheet particles smaller than 10 µm in size and less than 1 µm in thickness, and an estimated aspect ratio of about 10.

[0094] Compared to carrier 1, carrier 2 exhibits a relatively higher surface area and a very high water absorption rate, but a very low crushing strength. Carrier 2 is unimodal, with a unimodal pore size distribution centered at 2.4 µm, and no pores smaller than 0.3 µm (see [link to carrier 1]). Figure 16 ). Figure 18 The fractured SEM images also showed a highly lamellar morphology similar to that of carrier 1, but appeared slightly larger and thinner, which may have resulted in a slightly larger surface area of ​​carrier 2.

[0095] Carrier 3 also has a sheet-like morphology (see...) Figure 19 It has a single-mode aperture distribution (see) Figure 16 It has a low surface area and is very similar to carrier 1, but has excellent crushing strength. However, carrier 3 has an unexpectedly low water absorption rate.

[0096] Carrier 4 exhibits a relatively high surface area (1.23), a very high water absorption rate (75%), and excellent crushing strength. Figure 16 HgPVD in the sample revealed a single-mode pore size distribution centered at 2.4 µm, with no pores smaller than 0.3 µm. SEM of the fractured surface of support 4 showed a very uniform flaky particle morphology (mostly well-defined hexagons) and open pores (see [reference]). Figure 20A The plate-like particles have a size of approximately 5 µm and a thickness that varies between approximately 0.2 µm and 0.5 µm, providing an estimated aspect ratio of up to 25. The small particle size and high aspect ratio contribute to the high surface area achieved by carrier 4.

[0097] Supports 1-4 are intended to be suitable as supports for silver-based epoxidation catalysts as described in this disclosure. Supports 1-4 are intended to contain a high concentration of molybdenum oxide, which may negatively impact support performance; however, as observed in Example 2, most of the molybdenum oxide may be removed from the flake alumina powder via sublimation during high-temperature calcination. This was also observed for supports 1-4; for example, the calculated MoO3 content of support 4 was about 2%, but as shown in Table 4C, the calcined support 4 contained only about 0.14% MoO3. A simple wash of support 4 with 0.025M NaOH solution further reduced the MoO3 content in support 4 to 0.03%, i.e., about 99% of the MoO3 was removed from the original loading. The remaining MoO3 in the washed support 4 may remain deep within the grain boundaries, which may not significantly affect support performance.

[0098] The washed carrier 4 retained most of its properties, including surface area (approximately 1.2), water absorption (approximately 74%), and crushing strength (approximately 105 N). Figure 20A and 20B SEM images of the fractured surface of carrier 4 show that the carrier 4 has almost the same sheet-like morphology before and after washing. Figure 21 The study shows HgPVD with a very similar single-mode pore size distribution before and after washing.

[0099] Although this disclosure has been specifically shown and described with respect to its preferred embodiments, those skilled in the art will understand that the foregoing and other changes in form and detail may be made without departing from the spirit and scope of this disclosure. Therefore, it is intended that this disclosure be limited to the exact forms and details described and shown, but fall within the scope of the appended claims.

Claims

1. A method for forming alumina powder with a flake-like morphology, the method comprising: An aqueous slurry is formed, the aqueous slurry comprising an alumina source and a flux, wherein the flux has the chemical formula MO3, wherein M is a metal selected from Cr, Mo and W, and wherein the flux is present in the aqueous slurry in an amount of about 0.1 wt% to about 5 wt% based on the total weight of the alumina source; Dry the slurry to provide a solid product; as well as The solid product is calcined at a temperature above approximately 1200°C to convert it into an alumina powder that is essentially entirely in flake form.

2. The method according to claim 1, wherein M is Mo.

3. The method according to claim 1, wherein M is W.

4. The method of claim 1, wherein the flux is present in the aqueous slurry in an amount of about 0.1% to about 5% by weight, based on the total weight of the alumina source.

5. The method according to claim 1, wherein the alumina source comprises transition alumina.

6. The method according to claim 1, wherein the transition alumina comprises hydrated alumina.

7. The method of claim 1, wherein the alumina source is present in the aqueous slurry in an amount of about 10% to about 80% by weight.

8. The method of claim 1, wherein the slurry further comprises silica, and the silica is present in the aqueous slurry in an amount of about 0.1% to about 5% by weight, based on the total weight of the alumina source.

9. The method of claim 1, wherein the substantially entirely flake-shaped alumina powder comprises more than 96% flake-shaped particles.

10. The method of claim 1, wherein the substantially entirely flake-shaped alumina powder comprises 100% flake-shaped particles.

11. The method of claim 1, wherein the substantially entirely flake-shaped alumina powder has a flake particle aspect ratio of 5:1 or greater.

12. A method for forming an alumina support, the method comprising: A flux is added to a carrier composition comprising an alumina source, wherein the flux has the chemical formula MO3, wherein M is a metal selected from Cr, Mo and W, and wherein the flux is added in an amount of about 0.1% to about 5% by weight based on the total weight of the alumina source. The flux and the carrier composition are mixed to provide an admixture of the flux and the carrier composition; The mixture is molded into a molded body; as well as The molded body is calcined at a temperature above approximately 1200°C to transform it into an alumina carrier that is substantially entirely sheet-like.

13. The method of claim 12, wherein M is Mo, and the flux comprises ammonium molybdate.

14. The method of claim 12, wherein M is W, and the flux comprises ammonium metatungstate.

15. The method of claim 12, wherein the flux is added in an amount of about 0.1% to about 5% by weight, based on the total weight of the alumina source.

16. The method of claim 12, wherein the alumina source comprises transition alumina.

17. The method of claim 12, wherein the transition alumina comprises hydrated alumina.

18. The method of claim 12, wherein the carrier composition further comprises silicon dioxide, and the silicon dioxide is present in the carrier composition in an amount of about 0.1% to about 5% by weight based on the total weight of the alumina source.

19. The method of claim 12, wherein the substantially entirely sheet-like alumina carrier comprises more than 96% sheet-like particles.

20. The method of claim 12, wherein the substantially entirely flake-shaped alumina comprises 100% flake-shaped particles.

21. The method of claim 12, wherein the substantially entirely sheet-like alumina carrier has a sheet particle aspect ratio of 5:1 or greater.

22. The method of claim 12, wherein the substantially entirely sheet-like alumina support has a thickness of about 0.2 m. 2 / gm to approximately 2m 2 The surface area is approximately 30% to approximately 90%, the mercury porosimeter volume is approximately 0.3 ml / g to approximately 0.9 ml / g, and the average crushing strength is approximately 5 N to approximately 200 N.

23. The method of claim 12, wherein the substantially entirely sheet-like alumina support contains less than 1% porosity, the pore volume of which is less than 0.3 µm.

24. The method of claim 12, wherein the modal pore size of the substantially entirely sheet-like alumina carrier is in the range of about 0.5 µm to about 5 µm.

Citation Information

Patent Citations

  • Silver catalyst

    US3563914A

  • Chemical production of metallic silver deposits

    US3702259A

  • Ethylene oxide catalyst and process for preparing the catalyst

    US4761394A

  • Ethylene oxide catalyst and process for preparing the catalyst

    US4766105A

  • Catalyst composition for oxidation of ethylene to ethylene oxide

    US4908343A